International relations and the problem of difference - Inayatullah, Naeem (Routledge, 2004)
International Relations and the Problem of Difference has developed out of the sense that IR as a discipline does not assess the quality of cultural interactions that shape, and are shaped by, the changing structures and processes of the international system. In this work, the authors re-imagine IR as a uniquely placed site for the study of differences as organized explicitly around the exploration of the relation of wholes and parts and sameness and difference-and always the one in relation to the other.
Keywords: Intercultural communication.; Ethnicity.; International relations.; International economic relations.; Ethnicité.; Relations internationales.; Communication interculturelle.; ethnicity.; international relations.; POLITICAL SCIENCE -- Globalization.; Ethnicity; Intercultural communication; International economic relations; International relations; Electronic books.